Music of Festive Days in 18th Century Český Krumlov. Depiction of Festivities in an 18th Century Monastic Chronicle - Markéta Králová (Theatrum Historiae)
The principal and yet unpublished source for this study, the chronicle Liber magistralis I–V, was led by the Minorite friars in Český Krumlov between the years 1678 and 1948. The chronicle entries illuminate in detail the course and form of extraordinary days in this renowned South Bohemian town, including the festive events connected with the prominent noble family of Schwarzenbergs. The article is primarily focused on 500 chronicle pages written in the course of 26 years by the highly educated superior Hyacinth Sperl (1726–1750). Sperl described not only the festivities held in the Krumlov friary itself but also the castle and municipal feasts in which he participated. The superior was very attentive to musical affairs in his surroundings which he did not hesitate to depict colourfully within the monastic chronicle. On this basis, the content and settings of Schwarzenberg birthdays, magnificent triumphal entries, or municipal pilgrimage feasts can be reconstructed. To get a comprehensive image of noble musical activities, this research also draws on preserved Schwarzenberg personal correspondence. The forms of music and liturgy used in Český Krumlov during this era apparently followed Viennese Imperial patterns in various aspects. As there is no relevant literature addressing the topic of music relations between the Minorite Order and a noble family in the Habsburg hereditary lands in the 18th century, this study presents a unique illustration of such interconnection.